(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
To date, many studies have defined COPD-bronchial asthma crossover syndrome as a phenotype of COPD. Patients with a cross between bronchial asthma and chronic obstructive pulmonary disease (COPD) have differences with patients with isolated bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD). Separation of such patients into a special group seems to be justified and appropriate from the standpoint of pathophysiology, clinic and therapy.